2020
DOI: 10.1002/jcph.1618
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics and Pharmacodynamics of Norvancomycin in Children With Malignant Hematological Disease

Abstract: Knowledge of pharmacokinetic (PK) behavior of norvancomycin (NVCM) in pediatric patients is lacking, which leads to empirical therapy in clinical practice. This study developed a population PK model of children aged 0‐15 years; 112 opportunistic samples in total from 90 children were analyzed. The stability and prediction of the final model were evaluated by goodness‐of‐fit plots, nonparametric bootstrap, visual predictive check, and normalized prediction distribution errors. The PKs of NVCM in children was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The antibacterial spectrum, antibacterial activity, and adverse reactions of norvancomycin are similar to those of vancomycin. 1 Blood concentrations of vancomycin and norvancomycin vary greatly in different patients. Additionally, renal insufficiency can slow down the elimination of both drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial spectrum, antibacterial activity, and adverse reactions of norvancomycin are similar to those of vancomycin. 1 Blood concentrations of vancomycin and norvancomycin vary greatly in different patients. Additionally, renal insufficiency can slow down the elimination of both drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The population pharmacokinetics (PPK) analysis is a practical method to evaluate the pharmacokinetic characteristics and exposure of drug to obtain individual dosing in a target population ( Buil-Bruna et al, 2016 ; Chen et al, 2017 ; Wang et al, 2020 ). PPK models of PEM in NSCLC patients in the Netherlands ( Visser et al, 2019 ), India ( Srinivasan et al, 2019 ) and the United States ( Latz et al, 2006 ) have been reported and the clinical applicability of these models has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%